Decreased Glycogenolysis by miR-338-3p Promotes Regional Glycogen Accumulation Within the Spinal Cord of Amyotrophic Lateral Sclerosis Mice - Li, Chunyu; Wei, Qianqian; Gu, Xiaojing; Chen, Yongping; Chen, Xueping; Cao, Bei; Ou, Ruwei; Shang, Huifang (Frontiers in Molecular Neuroscience, 2019)
Metabolic dysfunction is a hallmark of aging-related neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). But the crosstalk between metabolic alteration and disease progression in ALS is still largely unknown. Glycogen, a branched polymer of glucose residues, is identified as the energy reserve of central nervous system (CNS), where its aberrant accumulation leads to neurodegeneration. Glycogen was reported to be accumulated in both CNS and visceral organs of SOD1G93A mice, a well-known ALS model, and contributes to pathological process of ALS. However, the accumulative patterns and mechanisms are not well elucidated. Here, we provide extensive evidence to show that glycogen accumulated in the lumbar spinal cord of ALS mice along with the disease progression, but not in the motor cortex. This regional accumulation of glycogen was caused by deteriorated glycogenolysis, which was triggered by decreased PYGB (glycogen phosphorylase, brain form). Moreover, miR-338-3p, an elevated miRNA in the spinal cord of SOD1G93A mice, directly targeted PYGB and was responsible for the decreased glycogenolysis and subsequent glycogen accumulation. Our work is helpful for better understanding of metabolic dysfunctions in ALS and provides novel targets for the therapeutic intervention in the future.